Decorated silver nanoparticles on biodegradable magnetic chitosan/starch composite: Investigation of its cytotoxicity, antioxidant and anti-human breast cancer properties. Issue 6 (December 2021) - He, Chenyang; Guo, Yu; Karmakar, Bikash; El-kott, Attalla; Ahmed, Ahmed Ezzat; Khames, Ahmed
Abstract: Nanotechnology is the field to yield modern systems, tools, and materials by controlling at the atomic and molecular levels using the features that appear on those surfaces. Applications for nanotechnology in medical diagnostics, food, medicine, biotechnology, environment, energy, chemistry, physics, etc, introduce this technology as an interdisciplinary and cross-sectoral context. In the current years, conjugated bio-nanomaterials involving magnetic core are a promising platform in new generation biological composites. In this regard, we report herein a novel Ag NPs supported chitosan-starch composite functionalized Fe3 O4, a dual core-shell type nanoparticle (Fe3 O4 @CS-Starch/Ag). In the oncological part of the recent study, the treated cells with Fe3 O4 @CS-Starch/Ag nanocomposite were assessed by MTT assay for 48 h about the cytotoxicity and anti-breast carcinoma properties on normal (HUVEC) and breast carcinoma cell lines i.e. Hs 578Bst, Hs 319. T, UACC-3133, UACC-732, and MDA-MB-453. The post-synthetically modified biogenic material was analyzed in detail over several physicochemical methods like, field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDS), energy dispersive X-ray analysis (EDX) elemental mapping, transmission electron microscopy (TEM), vibrating-sample magnetometer (VSM), X-ray diffraction analysis (XRD), and inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis. The viability of breast carcinoma cell lines reduced dose-dependently in Fe3 O4 @CS-Starch/Ag nanocomposite. The IC50 of Fe3 O4 @CS-Starch/Ag nanocomposite was 183, 207, 194, 279, and 252 µg/mL against Hs 578Bst, Hs 319. T, UACC-3133, UACC-732, and MDA-MB-453 cell lines, respectively. Graphical Abstract: ga1 Highlights: Decorated Silver nanoparticles on biodegradable magnetic chitosan/starch composite. chitosan/starch composite acted as reducing and stabilizing agent. Fe3 O4 @CS-Starch/Ag nanocomposite shown good antioxidant effects. Fe3 O4 @CS-Starch/Ag nanocomposite shown good anti-human breast cancer properties.